Kinetic study of dissociation of a copper(II) complex of a 14-membered tetraaza-macrocyclic ligand containing pyridine and pendant N-carboxymethyl arms - Lubal, Premysl (2015)
The kinetics of acid-catalyzed dissociation of the copper(II) complex with 7-methyl-3,7,11,17-tetraazabicyclo[11.3.1] heptadeca-1(17), 13,15-triene-3,11-diacetic acid (ac(2)Me[14] pyN(4)) at [H+] = 0.05-0.25 mol l(-1), I = 0.25 mol l(-1) (Na, H) ClO4, and T = 298.16 K was studied with conventional and stopped-flow UV/VIS spectroscopy. Three steps of consecutive complex reaction were observed. The very fast first and second steps characterized by k(1) = 70 +/- 10 and k(2) = 0.23 +/- 0.01 l mol(-1) s(-1) depend on the H+ concentration. The third step is very slow, k(3) = (1.08 +/- 0.03) x 10(-3) s(-1), and does not depend on the H+ concentration. Latter rate-determining step involves an isomerisation process forcing the copper(II) ion to leave rapidly the macrocyclic cavity. The reaction mechanism of the complex dissociation has been proposed, taking into account the results obtained for related systems by independent methods: potentiometry, UV/VIS and EPR spectroscopies, X-ray diffraction analysis, and molecular mechanics calculations.